2021
DOI: 10.37631/populika.v9i2.316
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Sekolah Ramah Anak Di SDN Lempuyangwangi Kota Yogyakarta

Abstract: Penelitian dilatarbelakangi oleh keprihatinan dunia pendidikan terhadap berbagai kasus yang kerap terjadi di sekolah. Dari data KPAI sepanjang Januari hingga April 2019 menyebutkan, pelanggaran hak anak masih terjadi dan didominasi perundungan, yaitu berupa kekerasan fisik, kekerasan psikis, dan kekerasan seksual, dan anak menjadi korban kebijakan. Sekolah Ramah Anak merupakan salah satu kebijakan yang dilakukan sebagai upaya pencegahan dalam mengatasi berbagai permasalahan yang melanggar hak anak terutama ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…One of the things that include respecting children's rights is that children must get a learning environment with proper facilities and infrastructure. This is related to the opinion of Utami et al (2017), which revealed that childfriendly schools could provide opportunities for students to carry out the learning process comfortably and not feel dangerous or threatening. In addition to the psychological aspects realized in child-friendly schools, physical aspects such as facilities or facilities and infrastructure provided by schools must meet ergonomic criteria according to the needs of children (Diyanti et al, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…One of the things that include respecting children's rights is that children must get a learning environment with proper facilities and infrastructure. This is related to the opinion of Utami et al (2017), which revealed that childfriendly schools could provide opportunities for students to carry out the learning process comfortably and not feel dangerous or threatening. In addition to the psychological aspects realized in child-friendly schools, physical aspects such as facilities or facilities and infrastructure provided by schools must meet ergonomic criteria according to the needs of children (Diyanti et al, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…Dalam hasil penelitian yang telah diuraikan sebelumnya menunjukkan bahwa penerapan Sekolah Ramah Anak (SRA) di SMAN 1 Surakarta untuk mengajarkan siswa tentang Hak Asasi Manusia dan nilai-nilai kemanusiaan serta menghargai perbedaan dengan orang lain. Program ini merupakan kebijakan yang diterapkan oleh Pemerintah Indonesia untuk menciptakan lingkungan belajar yang ramah anak dan mencegah berbagai pelanggaran hak-hak anak, khususnya di sekolah (Utami, Kusumawiranti, & Mali, 2021). Menurut Susanti, Rachman, & Ananda, (2021) terdapat kriteria untuk menjadi Sekolah Ramah Anak (SRA), yaitu: (1) pencanangan sebagai Sekolah Ramah Anak (SRA); (2) melaksanakan program untuk mendukung hak-hak anak; (3) pendidik dan tenaga kependidikan mengikuti pelatihan hak-hak anak; (4) sarana dan prasarana pendukung; (5) keterlibatan anak; dan (6) keterlibatan orang tua dalam penerapan Sekolah Ramah Anak (SRA).…”
Section: Penerapan Sekolah Ramah Anak (Sra) Dan Duta Sekolah Ramah An...unclassified
“…A CFS can protect kids from abuse, discrimination, and other ill-treatment, uphold kids' rights, and recognise their accomplishments. It also encourages kids to participate in decisions that affect them, like learning processes, planning, and complaints (Cobanoglu & Sevim, 2019;Fauziati, 2016;Fitriani et al, 2021;Utami et al, 2021).…”
Section: Introductionmentioning
confidence: 99%